REAL-TIME CLOUD ARCHITECTURE IN EDUCATIONAL SYSTEMS: A FRAMEWORK FOR SCALABLE AND PERSONALIZED LEARNING ENVIRONMENTS - Varshini Choudary Nuvvula (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2024)
The widespread adoption of cloud technologies in educational settings has fundamentally transformed the landscape of modern learning. This article examines how cloud-based infrastructures revolutionize education through enhanced accessibility, scalability, and real-time personalization capabilities. By analyzing the implementation of cloud technologies in educational institutions across multiple geographical regions, this article demonstrates how scalable transaction systems support massive open online courses (MOOCs) and digital learning platforms while maintaining optimal performance levels. The article explores how real-time optimization algorithms facilitate personalized learning paths through continuous assessment of student performance data, enabling dynamic content adaptation and immediate feedback mechanisms. Furthermore, this article addresses critical ethical considerations, including data privacy concerns and digital divide challenges, presenting a balanced analysis of both opportunities and potential drawbacks of cloud-driven educational transformation. The findings suggest that while cloud technologies offer unprecedented opportunities for democratizing education and enhancing learning outcomes, careful consideration must be given to infrastructure development, policy frameworks, and ethical guidelines to ensure equitable access and sustainable implementation. This article contributes to the growing literature on educational technology by providing a comprehensive framework for understanding the intersection of cloud computing and modern pedagogical approaches.